Rethinking Fascism and Dictatorship in Europe
XXVII, 317 p.
Keywords: Fascism exerted a crucial ideological and political influence across Europe and beyond. Its appeal reached much further than the expanding transnational circle of 'fascists', crossing into the territory of the mainstream, authoritarian, and traditional right. Meanwhile, fascism's seemingly inexorable rise unfolded against the backdrop of a dramatic shift towards dictatorship in large parts of Europe during the 1920s and especially 1930s. These dictatorships shared a growing conviction that 'fascism' was the driving force of a new, post-liberal, fiercely nationalist and anti-communist order. The ten contributions to this volume seek to capture, theoretically and empirically, the complex transnational dynamic between interwar dictatorships. This dynamic, involving diffusion of ideas and practices, cross-fertilisation, and reflexive adaptation, muddied the boundaries between 'fascist' and 'authoritarian' constituencies of the interwar European right.